Perception of Pre-Service Teachers Towards Using Nearpod as an Active Learning Tool (Journal of Informatics Education and Research, 2025)
The extensive use of Information and technology has transformed students into digital students, so teachers also use technology to attract students to their learning. Teachers used smart boards, projectors, tablets, etc. in the classrooms for active learning. Technology plays an important role in today’s scenario.  In this study researcher uses Nearpod as an active learning tool, with the help of this tool teacher create interactive lessons, and contains assessments in the form of quizzes, polls, videos, collaborative board which all are in one place in Nearpod. This platform is designed to enhance student engagement, participation and interactive learning experiences. It is helpful for both teachers and students also.  The aim of this study is to find out the perception of pre-service teachers towards Nearpod as an Active learning platform. For this study researcher selected Section A which has 50 Pre-Service teachers from the Lloyd College of Education of Greater Noida, Gautam Budh Nagar District. To achieve the objective of perception towards Nearpod, a survey method using a questionnaire is used. Primary data is used to collect information on the perception towards Nearpod from students. The findings show that students have a positive attitude towards using Nearpod.